Optimal Team Practice: The Way Forward. Issue 2 (April 2019) - Kidd, Vasco Deon; Cawley, James F.; Cloutier, Dagan; Tankersley, Dennis
Abstract : Optimal team practice (OTP) represents an amendment to an existing American Academy of PAs policy, Guidelines for State Regulation of PAs (HP-3500.3.4), that advocates for expanded access to affordable, high-quality healthcare through modernization of PA–practice laws. OTP also calls for PAs to practice without a collaborative or supervisory agreement with a specific physician, enabling practice-level decisions about collaboration. However, OTP remains poorly understood and relatively under-researched. This article analyzes OTP and its potential implications on legislative efforts, training of PAs, and practice level changes.